Comparative study of Korean White Ginseng and Korean Red Ginseng on efficacies of OVA-induced asthma model in mice - Lim, Chi-Yeon (J Ginseng Res, 2014)
BACKGROUND: Korean ginseng is a well-known medicinal herb that has been widely used in traditional medicine to treat various diseases, including asthma. Ginseng can be classified as white ginseng (WG) or red ginseng (RG), according to processing conditions. In this study, the authors compared the efficacies of these two ginseng types in a mouse model of acute asthma. METHODS: To produce the acute asthma model, BALB/c mice were sensitized with ovalbumin (OVA) and aluminum hydroxide, and then challenged with OVA. WG and RG extracts were administered to mice orally. The influences of WG and RG on airway hyperresponsiveness (AHR), immune cell distributions in bronchoalveolar lavage fluid (BALF), and OVA-specific immunoglobulin E (IgE), IgG1, and IgG2a in serum were investigated. Cytokine production by lymphocytes isolated from peribronchial lymph nodes and histopathological changes was also examined. RESULTS: In OVA-sensitized mice, both WG and RG reduced AHR and suppressed immune cell infiltration in bronchoalveolar regions. BALF OVA-specific IgE levels were significantly lower in RG-treated OVA-sensitized mice than in the OVA-sensitized control group. WG and RG also suppressed inflammatory cytokine production by peribronchial lymphocytes. Histopathological findings showed reduced inflammatory cell infiltration and airway remodeling (e.g., epithelial hyperplasia) in WG- and RG-treated OVA mice compared with OVA controls. CONCLUSION: In this study, WG and RG showed antiasthmatic effects in an OVA-sensitized mouse model, and the efficacies of RG were found to be better than those of WG.